(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
"Todaythe subject apprehends himself elsewhere, and ’subjectivity’ can return atanother place on the spiral: deconstructed, taken apart, shifted, withoutanchorage: why should I not speak of ’myself’ since this ’my’ is no longer the’self’?"